2015
DOI: 10.17113/ftb.53.02.15.4151
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Cultivars and Industrial Processing on Polyphenols in Sour Cherry (Prunus cerasus L.) Concentrated Juices

Abstract: The objective of this study is to investigate the influence of cultivar and industrial processing on total polyphenols, anthocyanins, hydroxycinnamic acids and antioxidant activity in concentrated sour cherry ( L cvs. Marasca and Oblačinska) juices. Samples were collected during four processing steps: from fresh fruit prior to processing, then from pressed, filtered and concentrated juices. The content of total phenols was the same in both cultivars, but antioxidant activity (Oblačinska>Marasca) and total mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
4
17
0
Order By: Relevance
“…GM TP value of 3.97 mg GAE mL −1 (Table ) confirmed the abundance of phenolic compounds in tested sour cherry juices, showing their good potential for use in functional food products, including smoothies, which are listed very high on the consumers’ list of desirable fruit‐based products. Obtained results are in accordance with previous investigations (Damar & Eksi, ; Khoo et al., ; Papp et al., ; Pissard et al., ; Repajić et al., ; Toydemir et al., ; Wojdyło et al., ). Data presented in Table showed highly significant differences in TP amount between cultivars ( p ≤ 0.01).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…GM TP value of 3.97 mg GAE mL −1 (Table ) confirmed the abundance of phenolic compounds in tested sour cherry juices, showing their good potential for use in functional food products, including smoothies, which are listed very high on the consumers’ list of desirable fruit‐based products. Obtained results are in accordance with previous investigations (Damar & Eksi, ; Khoo et al., ; Papp et al., ; Pissard et al., ; Repajić et al., ; Toydemir et al., ; Wojdyło et al., ). Data presented in Table showed highly significant differences in TP amount between cultivars ( p ≤ 0.01).…”
Section: Resultssupporting
confidence: 92%
“…As cultivars with higher SS content increase profitability of concentrated juice production, Maraska and Oblačinska could be more suitable for concentrated juice manufacturers. These cultivars previously showed their suitability for the production of concentrated juice with regard to their polyphenolic content (Repajić et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of the same compounds in sour cherry products was confirmed by Kirakosyan et al (2009) and in dried sour cherry by Zorić et al (2014). Only four anthocyanin compounds were reported in the study by Repajić et al (2015), but they also reported that the dominant compounds in sour cherry juice are cyanidin-3-O-glucosyl-rutinoside and cyanidin-3-Orutinoside.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have demonstrated that sour cherries exhibit anticarcinogenic effect in various colon cancer models (Ferreti et al, 2010). Furthermore, anthocyanins were identified as anti-inflammatory agents, which are major contributors to the antioxidant activity in cherries (Ferreti et al, 2010;Repajić et al, 2015). The total anthocyanin content of sour cherries is reported to range from 28 to 80 mg 100 g -1 (Blando et al, 2004).…”
Section: Introductionmentioning
confidence: 99%